Correlation between Arterial Lactate and Central Venous Lactate in Children with Sepsis - Jaime Fernández Sarmiento; Paula Araque; María Yepes; Hernando Mulett; Ximena Tovar; Fabio Rodriguez (Critical Care Research and Practice)
Introduction. Lactate is an important indicator of tissue perfusion. The objective of this study is to evaluate if there are significant differences between the arterial and central venous measurement of lactate in pediatric patients with sepsis and/or septic shock. Methods. Longitudinal retrospective observational study. Forty-two patients were included between the age of 1 month and 17 years, with a diagnosis of sepsis and septic shock, who were admitted to the intensive care unit of a university referral hospital. The lactate value obtained from an arterial blood sample and a central venous blood sample drawn simultaneously, and within 24 hours of admission to the unit, was recorded. Results. The median age was 2.3 years (RIC 0,3–15), with a predominance of males (71.4%), having a 2.5 : 1 ratio to females. Most of the patients had septic shock (78.5%) of pulmonary origin (50.0%), followed by those of gastrointestinal origin (26.1%). Using Spearman’s Rho, a 0.872 (p<0.001) correlation was found between arterial and venous lactate, which did not vary when adjusted for age (p<0.05) and the use of vasoactive drugs (p<0.05). Conclusion. There is a good correlation between arterial and venous lactate in pediatric patients with sepsis and septic shock, which is not affected by demographic variables or type of vasoactive support.